Nghiên cứu ứng dụng AI khả diễn trong FinTech: Tối ưu hóa đầu tư bền vững dựa trên tiêu chí ESG tại Việt Nam - Hoang, Anh; Le Vu Uyen, Phuong; Nguyen Minh, Man; Vo Huynh Yen, Nhi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study explores the role of eXplainable AI (XAI) in driving sustainable investment strategies within the financial technology (FinTech) sector in Vietnam. While AI models contribute to improving the efficiency of investment decision-making, transparency constraints are a significant barrier to the integration of Environmental, Social, and Governance (ESG) criteria. XAI is seen as a potential solution to address this issue by enhancing transparency, improving explainability, and ensuring accountability to strengthen investor confidence in the decision-making process. In the context of Vietnam's evolving landscape of AI and Big Data, along with the high growth potential of FinTech technology and applications: this study conducts a secondary data analysis of financial and ESG reports and applies advanced AI models combined with the SHAP mathematical framework to demonstrate how XAI can enhance resource allocation efficiency, risk management, and long-term sustainable development.
Keywords: XAI; Fintech; Sustainable Investment; ESG